Answer:
x = 3
y = 2
Explanation:
3x + 2y = 12
-2x + 3y = 5 to find the solution we will use elimination method and for that, multiply second equation with 3 and the first equation with 2
2 * 3x + 2y = 12
6x + 4y = 24
3 * -2x + 3y = 5
-6x + 9y = 15 now find the sum of both equation:
6x + 4y -6x + 9y = 24 + 15 add like terms
13y = 39 divide both sides by 13
y = 3 now that we found the value of y we can use this to calculate the value of x
3x + 2y = 12 replace y with 3
3x + 2*2 = 12
3x + 4 = 12 subtract 4 from both sides
3x = 9 divide both sides by 3
x = 3